The cross-correlation between 3D cosmic shear and the integrated Sachs-Wolfe effect - Zieser, Britta; Merkel, Philipp M. (Monthly notices of the Royal Astronomical Society, 2016)
We present the first calculation of the cross-correlation between 3D cosmic shear and the integrated Sachs-Wolfe (iSW) effect. Both signals are combined in a single formalism, which permits the computation of the full covariance matrix. In order to avoid the uncertainties presented by the non-linear evolution of the matter power spectrum and intrinsic alignments of galaxies, our analysis is restricted to large scales, i.e. multipoles below ℓ = 1000. We demonstrate in a Fisher analysis that this reduction compared to other studies of 3D weak lensing extending to smaller scales is compensated by the information that is gained if the additional iSW signal and in particular its cross-correlation with lensing data are considered. Given the observational standards of upcoming weak-lensing surveys like Euclid, marginal errors on cosmological parameters decrease by 10 per cent compared to a cosmic shear experiment if both types of information are combined without a cosmic wave background (CMB) prior. Once the constraining power of CMB data is added, the improvement becomes marginal.
Gesehen am 08.10.2021